Effect of Different Seed Treatments and Media on Growth and Biomass of Indian Cheese Maker - Withania coagulans (Stocks) Dunal. - L, Ram Mayur; Desai, B. S.; Jha, Sumankumar S.; Patel, D. P.; Hegde, H. T. (International Journal of Economic Plants, 2022)
The present investigation was conducted to assess the effect of different seed soaking treatments and media on growth and alkaloid content of Indian cheese maker–Withania coagulans (Stocks) Dunal. to develop effective nursery production technology. The experiment was conducted in completely randomized design with factorial concept, including twenty treatment combinations comprising of four levels of seed treatments with GA3 (0, 50, 100, 150 ppm) and five levels of different growing media. Among various concentrations of GA3 as pre-soaking treatment, 100 ppm GA3 (S3) showed significantly better results for germination, growth, biomass and alkaloid content in W. coagulans. Similarly, among growing media, red soil (M1) recorded maximum germination percentage, collar diameter, number of branches per plant, number of leaves per plant, total leaf area, length of the main root, thickness of main root, root dry biomass, shoot dry biomass, fresh weight of plant, dry weight of plant, survival percentage of the plant and total alkaloid content of plant. Overall, the result indicated that that pre-sowing W. coagulans seeds with GA3 -150 ppm for 24 hrs and subsequently sowing treated seeds in M1 media comprising of red soil (control) can enhance growth and alkaloid content.